Bioassay-direct fractionation and contact bioautography technique for antimicrobial activities of marine sponge - Darnis, Deny Susanti; Qaralleh, Haitham; Saad, Shahbudin; Syed Osman Idid, Syed Zahir Idid (2010)
The sponge (1L82008) possessed the highest antimicrobial activity among four sponges and three corals species investigated. The sponge tissue was extracted with methanol and followed with water and examined against two Gram-positive bacteria (Staphylococcus aureus and Bacillus anthracis), two gramnegative bacteria (Escherichia coli and Pseudomonas aeruginosa) and two fungi strains (Candida albicans and Cryptococcus neoformans) using disc diffusion method. The results showed that methanol extract had stronger antimicrobial activity against B. anthracis (400μg/disc) than water extract. Since the methanol extract was found to be active, it was used for further bioassay-directed fraction in order to isolate the active compounds. The dichloromethane and n-butanol fractions were found to be active at concentration 400μg/disc. Purification of n-butanol fraction was done by using normal phase column chromatography eluted with n-butanol:acetic acid:water (12:3:5). Based on thin layer chromatography (TLC) profiles, the same fractions were collected, concentrated and assayed for antimicrobial activity against B. fnthracis. The results showed that fractions (87-123) and fractions (124-183) were the most active fractions. The TLC of the active fractions were then developed using the same mobile phase and subjected to contact bioautography against B. anthracis, which showed inhibition zone at different retention time, indicating the presence of antimicrobial components.